Using evidence-based medicine to protect healthcare workers from pandemic influenza: Is it possible? - Gralton J; McLaws ML (Critical Care Medicine, 2011)
OBJECTIVE: To use evidence-based principles to develop infection control algorithms to ensure the protection of healthcare workers and the continuity of health service provision during a pandemic. DESIGN: : Evidence-based algorithms were developed from published research as well as 'needs and values' assessments. Research evidence was obtained from 97 studies reporting the protectiveness of antiviral prophylaxis, seasonal vaccination, and mask use. Needs and values assessments were undertaken by international experts in pandemic infection control and local healthcare workers. Opportunity and resources costs were not determined. SETTING: The Australian government commissioned the development of an evidence-based algorithm for inclusion in the 2008 revision of the Australian Health and Management Plan for Pandemic Influenza. PARTICIPANTS: Two international infection control teams responsible for healthcare worker safety during the Severe Acute Respiratory Syndrome outbreak reviewed the evidence-based algorithms. The algorithms were then reviewed for needs and values by eight local clinicians who were considered key frontline clinicians during the contain and sustain phases. The international teams reviewed for practicability of implementation, whereas local clinicians reviewed for clinician compliance. RESULTS: Despite strong evidence for vaccination and antiviral prophylaxis providing significant protection, clinicians believed they required the additional combinations of both masks and face shields. Despite the equivocal evidence for the efficacy of surgical and N95 masks and the provision of algorithms appropriate for the level of risk according to clinical care during a pandemic, clinicians still demanded N95 masks plus face shields in combination with prophylaxis and novel vaccination. CONCLUSIONS: Conventional evidence-based principles could not be applied to formulate recommendations due to the lack of pandemic-specific efficacy data of protection tools and the inherent unpredictability of pandemics. As an alternative, evidence-based principles have been used to formulate recommendations while giving priority to the needs and values of healthcare workers over the research evidence.